SYMBOLISM AND HARMONY OF CHARACTER IN CURRENT STORIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, the theme of the current Uzbek stories is colorful, the spirit of the hero, the character, the symbolism of traditional storytelling X.Dustmuhammad's work has been researched on an example. In it, the author's high artistic vision, romantic imagination, original artistic texture, artistic-aesthetic ideal, author's Worldview are shown on the example of several stories.